The Bible and the literary critic - Wilder, Amos Niven, 1895- (Minneapolis, MN Fortress, 1991)
Includes bibliographical references and index.
Keywords: Bible as literature; Bible -- hermeneutics; Bible -- criticism, interpretation, etc, -- history -- 20th century